2011
DOI: 10.1007/s12098-011-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Zinc in Reducing Hyperbilirubinemia among At-Risk Neonates: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Twice daily administration of oral zinc in a dose of 10 mg/day does not reduce the incidence of hyperbilirubinemia in at-risk term and late-preterm neonates during first wk of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Maamouri et al we're not able to show any significant difference in the incidence of hyperbilirubinemia among the two arms (zinc 26% vs. control 22%, p=0.206) 29 and similarly Rana et al also didn't report any significant difference in the incidence of hyperbilirubinemia in the zinc gluconate group when compared to placebo group (17.9% vs 19.1%; OR=0.95, 95% CI: 0.50-1.67; p=0.92) 32. …”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Maamouri et al we're not able to show any significant difference in the incidence of hyperbilirubinemia among the two arms (zinc 26% vs. control 22%, p=0.206) 29 and similarly Rana et al also didn't report any significant difference in the incidence of hyperbilirubinemia in the zinc gluconate group when compared to placebo group (17.9% vs 19.1%; OR=0.95, 95% CI: 0.50-1.67; p=0.92) 32. …”
mentioning
confidence: 67%
“…Only one study enrolled VLBW infants 30 used zinc gluconate and this was the largest study conducted till date. 32 The total neonates enrolled in these different RCT are 749 (zinc group 367 and control 382). Various outcomes were seen by the investigators in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies should be considered when evaluating the effect of zinc therapy in hyperbilirubinemic neonates. Kumar et al (6) , Rana et al (7) and also Maamouri et al (8) found that the incidents of hyperbilirubinemia and requriement of phototherapy did not differ with zinc supplemented neonates (the studies included all neonates, not only neonates with hyperbilirubinemia). As serum zinc level is higher in hyperbilirubinemic neonates (18) , zinc supplementation in addition to phototherapy may cause an increase in the serum zinc level and zinc toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although zinc has traditionally been known as a nontoxic element, nowadays it has been shown that free ionic zinc can potently injure neurons (17) . Recently some studies have proposed using zinc salts for lowering bilirubin levels in neonates, jaundice or preventing the incidents of neonatal jaundice (6,7,9,10) . The results of the studies should be considered when evaluating the effect of zinc therapy in hyperbilirubinemic neonates.…”
Section: Discussionmentioning
confidence: 99%
“…When given in high doses, zinc can interfere with absorption of micronutrients such as iron and copper [9], and compounds such as bilirubin. In another article published in this issue, Rana et al have tried to utilize this property of zinc in treatment of neonatal hyperbilirubinemia [10]. In this welldesigned study, the authors did not find any benefit of zinc supplementation in reducing the serum bilirubin at 72 h, risk of significant hyperbilirubinemia, or need of phototherapy.…”
mentioning
confidence: 97%